Interdependence between core and peripheries of the European economy: secular stagnation and growth in the Western Balkans - Will Bartlett; Ivana Prica (The European Journal of Comparative Economics, 2017)
European countries are economically dependent upon each other. This paper therefore embeds the analysis of the Western Balkan countries within a wider perspective of the European economy as a whole. It combines a simple core-periphery model with an under-consumption model to provide an explanation of the emergence of secular stagnation, the dependency relationships between the core and peripheries of the European economy, and the spillover effects of Eurozone crisis to the Western Balkans. Due to tendencies to under-consumption, the core countries have been vulnerable to secular stagnation. In order to overcome this tendency within the Eurozone they are dependent on export revenues from the peripheries to sustain their economic growth. This has led to high trade and current account deficits during the boom and placed the peripheries in a highly vulnerable position during the recession period. Financialisation of the European economy has emerged as a response to the tendency towards secular stagnation, as the provision of consumer credit stimulated demand and temporarily overcame under consumption tendencies. The paper argues that continuing austerity, as a method to create internal devaluation, is unlikely to succeed as a means to extricate the periphery countries from the crisis. Given the dependencies of the European economies upon one another, a possibly better way out of the current period of low growth and stagnation would be a coordinated fiscal expansion to stimulate domestic and Europe-wide demand.